Somatic Embryogenesis and Organogenesis in Teak (Tectona Grandis L.) - Lim, Sooi Ping (2008)
Teak is one of the most valuable timber trees of the tropics. Commercially, teak wood is prized for its strength, durability and appearance. The ever-increasing demand for teak timber has resulted in large-scale plantations, both within and outside its range of natural distribution. Nevertheless teak growers often faced difficulties in obtaining sufficient planting materials, particularly those with improved genetic qualities. During the past two decades, the shift towards teak biotechnology in teak improvement has taken place, away from traditional breeding programmes. Use of in vitro regeneration as an integral component of tree improvement programmes has been initiated for teak and may indeed be useful to overcome the handicaps associated with teak production. Therefore this project attempts (1) to study the production of callus and development of somatic embryos from embryogenic callus for genetic manipulation purposes, and (2) to develop an improved in vitro shoot multiplication and plant regeneration protocol. In the first study, teak callus was successfully induced and categorised into embryogenic and non-embryogenic callus. Based on morphological and anatomical observations, callus production from cotyledon and embryo explants showed similar morphological responses irrespective of plant growth regulators, media and incubation conditions. Among the six types of callus observed, only type A callus could be classified as embryogenic cell mass based on several criteria i.e. having relatively small (25-35μm) and isodiametric cells with distinct nucleus, contained dense cytoplasm rich in starch reserves, and were actively dividing. Type A callus was obtained from embryo explants that were cultured on either half or full strength MS medium with 1.0mgl-1 2,4-D and 1.0mgl-1 BAP, full strength MS medium with 1.0mgl-1 2,4-D and 2.0mgl-1 BAP and half strength MS medium with 2.0mgl-1 2,4-D and 1.0mgl-1 BAP. Only cultures that were incubated in the dark for 24 hours gave rise to embryogenic response. When the embryogenic callus was subcultured in liquid medium in several stages, early stage somatic embryos (globular and early heart stage) were obtained, before further development was arrested. The failure of the somatic embryos to mature beyond this stage was likely due to the requirements for specific maturation conditions. In the second study, proliferation of shoots was achieved with four types of explants namely shoot tip, node, cotyledon and zygotic embryo. The embryo explant was found to produce the highest number of shoots with an average of 9.3 shoots (76% response) per explant on MS medium with 2.0mgl-1 BAP and 0.01mgl-1 NAA. The microshoots from embryo explants developed well on elongation medium with 0.1mgl-1 BAP and subsequently developed stout roots on rooting medium with 0.01mgl-1 NAA. The successful initiation of early stage somatic embryos should be further explored by narrowing the concentration of growth regulators used in this study in order to increase the production of embryogenic callus as well to enhance the maturation of somatic embryos into whole plantlets. Concurrently the shoot proliferation medium that has been established in this study may well be utilised to regenerate the embryos